Social Inequality in the Perspective of Tafsir Al-Mishbah by M. Quraish Shihab: Thematic Interpretation Study of Tiktok Trends - Zakin, Agus Nur; Saerozi, Ahmad (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study examines the phenomenon of social inequality trends on TikTok through the perspective of Tafsir al-Mishbah by M. Quraish Shihab. It explores how Shihab interprets Qur'anic verses to construct a comprehensive understanding of social justice. The findings show that the trend of social inequality on TikTok reflects real and structural disparities in Indonesian society, particularly in terms of wealth, education, and employment. These digital representations highlight a deep-rooted crisis of justice that goes beyond economics. Shihab’s interpretations emphasize Islamic values such as justice (‘adl), balance (al-mīzān), and collective responsibility as foundational principles for addressing inequality. His readings of verses like QS. Al-Hasyr: 7, QS. Az-Zumar: 9, and QS. Al-Isra’: 35 offer an ethical and spiritual framework for understanding inequality as a moral issue. Thus, the findings affirm that Tafsir al-Mishbah can serve as a theological reference for raising collective awareness and developing solutions to the normalization of injustice in the digital era.